Luminescence properties of KAlP₂O₇ crystals doped with chromium ions - Gomenyuk, O.V.; Nedilko, S.G.; Stus, N.V.; Chukova, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Luminescence properties of the KAlP₂O₇ crystals doped with the chromium ions were investigated. Luminescence spectra consist of two main bands: one of them lies in the blue-green spectral region and the other lies in the red spectral region. The maximum positions of the bands depend on the crystal composition and temperature of the samples. The blue-green band consists at least of three components. Complex structure of the blue-green broad band results from a superposition of matrix intrinsic radiation and emission of the distorted CrO₄²⁻ groups, where chromium ions have 6+ ion charge. The red luminescence band and the narrow spectral lines observed for the chromium-doped KAlP₂O₇ crystals were assigned to electron transitions in the Cr³⁺ ions in octahedral oxygen surround. Structure peculiarities of the various types of the chromium luminescence centers formed in the investigated matrix are discussed.